Taking a deeper look at the biodiversity on temperate mesophotic reefs to inform adaptive management of impacts in Storm Bay, Tasmania - Ashlee Bastiaansen; Neville Barrett; Nicholas Perkins; Jacquomo Monk; Elisabeth M.A. Strain (Ecological Indicators, 2024)
Mesophotic reef assemblages in south-eastern Australia remain poorly described despite their growing vulnerability due to new pressures from expanding offshore industries such as aquaculture and renewable energy. To address this knowledge gap, imagery from Automated Underwater Vehicles offers an efficient method of obtaining initial baseline inventories and tracking changes in these under-studied mesophotic benthic ecosystems. Here, we characterise the composition of sessile epibenthic communities across a depth gradient (24 – 55 m) on three distinct offshore reef systems in western Storm Bay, Tasmania, a large embayment subject to increasing anthropogenic pressures. We sampled at two time points (2015 and 2020) and quantify components of variance to help select candidate indicator morphospecies. The shallower communities (<30 m) were dominated by macroalgae, mostly Caulerpa spp., while deeper communities (>30 m) were dominated by encrusting sponges and fine turfing biological matrices. From 2015 to 2020, there was a reduction in overall morphospecies diversity between depth zones across all three reefs, except in the shallowest zone. This was matched by declining Caulerpa depth range and cover. Further, there was a general decline in the cover of morphospecies groups with depth, as abundance became more concentrated on a few morphospecies, primarily matrix groups. Simulation-based power analysis showed that for most individual morphospecies, change in cover of +/- 50 % or less was not detectable with sufficient power, unless the survey design incorporated sampling across all three reefs. This was primarily because in our study system few individual morphospecies reached > 2 % cover, and hence greater sampling effort was required for adequate description. The prevalence of sparse morphospecies and generally low cover underscores the necessity for pilot studies to ascertain the required sampling effort for accurate quantification of biodiversity changes on mesophotic reefs.